Tourism activities in the frontline areas of Sumy region: problems, opportunities and prospects - Kornus, Olesia; Venherska, Natalia; Reimann, Mart; Kornus, Anatolii; Patsiuk, Viktoriia (Human Geography Journal, 2023)
The Sumy region has great and significant tourism potential. Before the Russo-Ukrainian War, the region had 3,465 historical and cultural monuments, including 367 architectural and urban planning monuments (five of them of national importance). Before the war, the tourism sector was developing steadily, with new types of tourism services and the formation of tourism clusters. However, Russia's Invasion of Ukraine resulted in a significant decrease in tax revenues, which has a negative impact on tourism. The purpose of this paper is to study the peculiarities and future prospects of tourism development in the Sumy region during the war, based on data from a sociological survey conducted in five Ukrainian frontline regions in the framework of the Estonian-Ukrainian research project "Development of Ukrainian frontline communities and tourism business during the war and future strategy", which was supported by the Estonian Research Agency.The sociological survey was conducted online and included 25 closed and open-ended questions. Survey results were processed using Microsoft Excel 2010 and SPSS Statistics V21.0. A total of 29 respondents (20.1%) from the Sumy region participated in the sociological survey, 69% of whom live in urban areas and 31% in rural areas. Analysis of the areas of activity of the tourism respondents from the Sumy region revealed that urban respondents were more representative of tourism businesses (tour operators, travel agents, sole proprietors, etc.), while rural respondents were predominantly representatives of tourist attractions (museums, educational and recreational facilities, etc.). Responses to the following questions were analyzed: pre-war tourism activities, wartime tourism activities, changes in tourism, prospects for tourism development, threats and opportunities for tourism development, problems in the tourism sector, prospects for tourism development, and advantages in cluster cooperation.